Handwritten Text and Music Recognition come risorsa per il Patrimonio Culturale - Ribuoli, Roberto (Archeomatica, 2023)
Data driven knowledge is revolutionizing many field of research, but handwritten cultural heritage doesn’t seem to be able to benefit from this innovation. But what if AI itself could provide a solution for the accessibility of documents? This article introduces the basic functioning and the latest developments of Handwritten Text and Music Recognition, Ai-based technologies that could provide archives and libraries, as well as museums, with a powerful tool to access on a scale their written content. We discuss the future perspectives with some of the leading experts in the field, focusing on the role this technology may play in connecting tangible documents and intangible cultural heritage.